The Effect Of Good Bureaucracy, Internal Control, Competency Development, And Soft Skills As Efforts To Improve Staff Performance With Entity Independence As An Intervening Variable - Ferdianingtyas Ferdianingtyas; Nursaid Nursaid; Trias Setyowati; Nurul Qomariah (UNIVED Press, 2026)
The organizations can leverage internal resources to enhance employee autonomy and performance, while ensuring that the organization operates more independently and effectively in achieving its goals. The study purpose to examine and analyze the effect of good bureaucracy, internal control, competency development, and soft skills on staff performance, both directly and through entity independence as a mediating variable. This study is explanatory research with a quantitative approach. The study population was all staffs of the Regional Financial and Asset Management Agency (BPKAD) of Jember Regency, and the sample was determined using a purposive sampling technique. Data analysis used the Structural Equation Modeling (SEM) method with the Partial Least Squares (PLS-SEM) approach. The results showed that good bureaucracy, competency development, and soft skills have significant effect on staff performance, while internal control insignificant effect on staff performance. Good bureaucracy, internal control, competency development, and soft skills have significant effect on entity independence. Entity independence have significant effect on staff performance. Entity independence roles as mediating in the effect of good bureaucracy, internal control, competency development, and soft skills on staff performance.